Tradisi Ritual Bulan Suro Dalam Perspektif Islam Didesa Telaga Jernih, Kecamatan Secanggang, Kabupaten Langkat - Cindy Artika; Sakti Ritonga; Ismail Ismail (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2024)
This research aims to find out the meaning and purpose in each implementation of the Suroan tradition from an Islamic perspective in the Javanese tribe by taking research in Telaga Jernih Village, Secanggang District, Langkat Regency. This type of research uses a qualitative descriptive method that describes how the Suroan tradition is implemented and what the Islamic perspective is. Data was obtained through observation, interviews and documentation, followed by descriptive narrative presentation and analysis of the data. Every ritual in Tealaga Jernih Village has a purpose and purpose, and each Javanese community understands it differently. A ritual or action cannot exist without a purpose. The reason a ritual is performed is because it is considered important, useful and beneficial. From an Islamic point of view, a tradition or culture basically has meaning and benefits for the community itself, so that there is no conflict in its implementation. The tradition of one Suro carried out by the people of Telaga Jernih does not conflict with Islamic Aqidah and sharia at all, because in every tradition of implementation there are Islamic values and teachings such as prayer, gratitude, socialization and friendship.